Computer-based speech training for children - Hua, Nong Ting; Yunus, Jasmy; Vandort, Sandra; Shaikh Salleh, Sheikh Hussain (Inderscience Publishers, 2004)
A computer-based speech training system has been developed for children. The system is able to perform diagnostics and training in Malay language at both syllable and word level. The system allows children with difficulty in articulating plosive sounds to train with the computer to correct their speech articulation problems. Besides that, the system also provides audio and visual feedback to make the children aware of their errors of articulation. Sixteen Malay monosyllables and 16 bisyllabic Malay words are selected as the stimulus items. All these syllables and words have a plosive consonant-vowel structure (CV or CVCV). The system tests showed that it has the potential to be used in schools, homes and speech therapy clinics.